2011
DOI: 10.1007/s11999-011-1949-0
|View full text |Cite
|
Sign up to set email alerts
|

Endosteal Strut Augment Reduces Complications Associated With Proximal Humeral Locking Plates

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 29 publications
7
67
0
1
Order By: Relevance
“…The perception of an improved physical and mental quality of life was greater in our group than the first surgery or bloodless treatment as reported in a meta-analysis (14). In the scientific literature, there is evidence that early mobilization (within one week) resulted in less pain and faster recovery in patients with stable fractures compared with a delayed mobilization (after three weeks) (16). Although aseptic non unions are not stable fractures (16), very limited evidence suggests similar outcomes for early versus delayed mobilization after surgical fixation (16).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Isupporting
confidence: 56%
See 1 more Smart Citation
“…The perception of an improved physical and mental quality of life was greater in our group than the first surgery or bloodless treatment as reported in a meta-analysis (14). In the scientific literature, there is evidence that early mobilization (within one week) resulted in less pain and faster recovery in patients with stable fractures compared with a delayed mobilization (after three weeks) (16). Although aseptic non unions are not stable fractures (16), very limited evidence suggests similar outcomes for early versus delayed mobilization after surgical fixation (16).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Isupporting
confidence: 56%
“…Some studies show that non union is a variable outcome, highly influenced by the perforation of the articular surface with screws or varus collapse, especially in comminuted osteoporotic bone fractures of the medial plateau (15). Adequate mechanical medial column support may be obtained by an anatomical reduction of the fracture and a medial cortical contact in the case of comminution, by placing an oblique locking screw from the inferomedial region of the proximal fragment (15,16). !…”
Section: Discussionmentioning
confidence: 99%
“…13 Later, Neviaser et al reported low rates of reduction loss (2.6%), screw cut-out (0%) and osteonecrosis (2.6%), as well as high clinical outcome scores in a series of 38 patients with displaced proximal humeral fractures treated with locking plate fixation and an endosteal strut augment. 19 Biomechanical testing showed that medial support with an intramedullary fibular graft and angular stable fixation increased the overall stiffness of the bone-implant construct and reduced migration of the humeral head fragment, as compared with the locking plate alone. [20][21][22][23] In cadaveric specimens, Chow et al showed how fibular allograft augmentation could increase the strength of the locking plate to withstand repetitive varus loading.…”
Section: Discussionmentioning
confidence: 99%
“…Although we were unable to compare the postoperative value with the preoperative value in this study, as we evaluated the functional scores only after surgery, the postoperative functional scores in this study was comparable to them in other previous studies. [15][16][17]22,23) In surgical intervention for the unstable proximal humerus fractures with osteoporosis, the anatomical reduction at the medial calcar has been emphasized; 7,11,12) in particular, if metaphyseal comminution is combined, and therefore anatomical reduction and its maintenance were not feasible, other options, such as inferomedial calcar screw or intramedullary strut bone graft, should be considered. Gardner et al 7) emphasized the importance of medial support (either by anatomical reduction of medial cortex or oblique locking screw placement for medial calcar support) in locking the plate fixation of proximal humerus fractures.…”
Section: Discussionmentioning
confidence: 99%
“…7) Previous investigators described the importance of anatomic reduction and mechanical support of medial calcar in proximal humerus fractures, reporting high failure rate or varus malunion without medial column support in cases of concomitant comminuted fracture at the medial calcar. [7][8][9][10][11][12] Since Walch et al 13) used the intramedullary bone peg technique in treating nonunion at the humeral surgical neck, Gardner et al 14) used a fibular strut allograft as an endosteal implant and support for proximal humerus fractures in small series [14][15][16][17][18] The purpose of this study was to investigate the clinical and radiological outcomes of locking plate fixation with a fibular strut allograft for unstable osteoporotic proximal humerus fractures. We hypothesized that the use of fibular strut allograft as an internal pillar may be a good option for preventing varus collapse and maintaining the initial reduction status.…”
Section: Introductionmentioning
confidence: 99%